The Trend of Interpersonal Violence Mortality at National and Provincial Levels in Iran From 1990 to 2015. Issue 21 (November 2021) - Amanat, Man; Naghdi, Khatereh; Saeedi Moghaddam, Sahar; Ahmadi, Naser; Rezaei, Nazila; Saadat, Soheil; Salehi, Mona; Mehdipour, Parinaz; Khosravi, Sepehr; Kianian, Farzaneh; Forootan, Elmira; Hosseini, Elnaz; et al.
Interpersonal violence (IPV) is a major public health concern with a significant impact on physical and mental health. This study was designed to evaluate age–sex-specific IPV mortality trends and the assault mechanisms (firearm, sharp objects, and other means), at national and provincial levels, in Iran. We used the Iranian Death Registration System (DRS) and the population and housing censuses in this analysis. Spatio-temporal and Gaussian Process Regression methods were used to adjust for inconsistencies at the provincial level and to integrate data from various sources. After assessing their validity, all records were reclassified according to the International Classification of Diseases, 10th Revision (ICD-10). All ICD-10 codes were then mapped to Global Burden of Disease (GBD) 2013 coding. More than 700 individuals died due to IPV in 1990 and more than twice this number in 2015. The IPV mortality age-standardized rate, per 100, 000, increased from 1.62 (95% Uncertainty Interval [UI] = [0.96, 2.75]) in 1990 to 1.81 [1.15, 2.89] in 2015. Among females, the age-standardized mortality rate at national level per 100, 000 due to IPV was 1.27 [0.66, 2.43] in 1990 and decreased to 1.08 [0.60, 1.96] in 2015. Among males, the age-standardized mortality rate was 1.96 [1.25, 3.09] in 1990 rising to 2.54 [1.70, 3.82] in 2015. Data from provinces revealed that during the period of our study, Hormozgan province had the largest increase of IPV among females, and Fars province had the largest increase of IPV among males. Conversely, the largest decrease was detected in West Azarbaijan and Qom provinces in females and males, respectively. This study showed a wide variation in the incidence and trends of IPV in Iran by age, sex, and location. The study has provided valuable information to reduce the burden of IPV in Iran and a means to monitor future progress through repeated analyses of the trends.